INTEGRATING SPUR GEAR TEETH DESIGN AND ITS ANALYSIS WITH G2 PARAMETRIC BÉZIER-LIKE CUBIC TRANSITION AND SPIRAL CURVES - YAHAYA, SAIFUDIN HAFIZ; HASOLOAN, HAERY IAN PIETER; YAAKOB, MOHD YUHAZRI (Global Engineers and Technologists Review, 2012)
An involute curve (or known as an approximated curve) is mostly used in designing the gear teeth (profile) especially in spur gear. Conversely, this study has the intention to redesign the spur gear teeth using the transition (S transition and C spiral) curves (also known as the exact curves) with curvature continuity (G2) as the degree of smoothness. Method of designing the transition curves is adapted from the circle to circle templates. The applicability of the new teeth model with the chosen material, Stainless Steel Grade 304 is determined using Linear Static Analysis, Fatigue Analysis and Design Efficiency (DE). Several concepts and the related examples are shown throughout this study.